CRITICAL THINKING SKILLS AND CREATIVITY ENHANCEMENT IN 7th GRADE STUDENTS THROUGH PBL MODEL AND JAS APPROACH (Jurnal Pendidikan IPA Indonesia, 2015)
This research aim is to improve  critical thinking skill dan creativity of student at VIIC class  in SMP 2 Kudus academic year 2013/2014 by implementing  problem-based learning (PBL) with Jelajah Alam Sekitar (JAS) approach. The study design used is classroom action research is conducted in  2 cycles. The first cycle apply PBL with JAS approach in which students conduct direct exploration to environment and in the second cycle students conduct direct and indirect exploration. The results showed that PBL model with JAS approach able to improve students’ critical thinking skills amounted to 74. 35% and enhance students’ creativity amounted to 66.96%. It can be concluded that the PBL model with JAS approach able to improve critical thinking skills and creativity of students effectively.